Transfer pricing documentation and country-by-country reporting : action 13 - 2015 final report - Organisation for Economic Co-operation and Development (OECD/G20 base erosion and profit shifting project, ISSN 2313-2604, 2015)
Summary.
Keywords: yritysverotus; siirtohinnat; verotus; kansainväliset yritykset